Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution - HALL, SALLY; THATJE, SVEN (Zootaxa, 2009)
Four new species of lithodid crab were identified in the collections of the National Museum of Natural History, Smithsonian Institution. These include three species of the genus Paralomis: P. nivosa from the Philippines, P. makarovi from the Bering Sea, and P. alcockiana from South Carolina; and one new species of the genus Lithodes, L. galapagensis, from the Galapagos archipelago. Two of these species, P. nivosa and P. makarovi were part of a collection of previously unidentified lithodid samples from the Albatross expeditions of 1906–1908. Paralomis makarovi may have been misidentified as P. multispina Benedict, 1894, or P. histrix (De Haan, 1844) in other collections owing to superficial similarities in carapace ornamentation and overlapping distributions.